Health professionals' perspectives on the discharge process and continuity of care for stroke survivors discharged home in regional Australia: A qualitative, descriptive study. (21st December 2018) - Kable, Ashley; Baker, Amanda; Pond, Dimity; Southgate, Erica; Turner, Alyna; Levi, Christopher
Abstract: Many stroke patients are discharged home due to advances in treatment approaches and reduced residual disability. The aim of this study was to understand health professionals' perspectives on the discharge process and continuity of care during the transition between hospital and home for stroke survivors. In this qualitative, descriptive study, we used focus groups with 25 health professionals involved in discharge processes for transition from hospital to home in 2014, in a regional area of Australia. Discontinuity in the discharge process was affected by pressure to discharge patients, discharge medications and associated risks, inadequate or late discharge summaries, and challenges involving carers. Discontinuity in post‐discharge services and follow up was affected by availability of post‐discharge services, number of services arranged at the time of discharge, general practitioner follow up after discharge, delays and waiting lists, carer problems, and long‐term follow up. There were complex organizational barriers to the continuity of care for stroke survivors discharged home. It is important to address these deficits so that stroke survivors and their carers can make the transition home with minimal risk and adequate support following a stroke.